BILIK PADI TRADISIONAL KERINCI (Arsitektur dan Seni Ukir) - Nofrial Nofrial; Purwo Prihatin; Wahyono Wahyono; Marten Agung Laksono (Corak : Jurnal Seni Kriya, 2019)
Kerinci traditional bilik padi are no longer functioning, their existence is almost extinct. Through observation, literature studies and interviews, it is known that bilik padi use pedestal, a peg system in stringing poles. The entire building is made of wood, the building enlarges upwards. Octagonal pillars, sirap roofs, small doors made under the roof of the roof. The carving motif comes from the shape of plants, forms of vines. Engraving is applied to poles, walls, lower and upper beams, and end of rafter.Keywords: Bilik Padi, Architecture and Carving Art Bilik padi tradisional Kerinci sudah tidak difungsikan lagi, keberadaannya hampir punah. Melalui observasi, studi pustaka dan wawancara diketahui bilik padi menggunakan batu umpak, sistem pasak dalam merangkai tiang dengan balok. Seluruh bangunan terbuat dari kayu, bangunan membesar ke atas. Tiang segi delapan, atap sirap, pintu dibuat kecil dibawah bubungan atap. Motif ukiran berasal dari bentuk tumbuh-tumbuhan, bentuk sulur-suluran. Ukiran diterapkan pada tiang, dinding, balok bawah dan atas, serta ujung kasau. Kata Kunci: Bilik Padi, Arsitektur dan Seni Ukir